2014
DOI: 10.1002/art.38795
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Radiographic and Symptomatic Hip Osteoarthritis in an Urban United States Community: The Framingham Osteoarthritis Study

Abstract: Objectives The last prevalence survey encompassing urban populations was part of the nationwide Health and Nutrition examination survey (NHANES I) in the 1970's. We carried out a prevalence survey for hip osteoarthritis (OA) in the Framingham Study Community cohort. Methods Persons age 50 and older living in Framingham in 2002 – 2005 were recruited by random digit dialing without respect to joint pain or arthritis. Anteroposterior standing long-limb radiographs of the lower extremities including the pelvis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 17 publications
8
89
0
8
Order By: Relevance
“…We included studies if they: (1) included human patients with OA, (2) had a sample size C1000, (3) reported the cost of OA (i.e., the total cost with or without cost subcategories) and/or HRQoL (either in summary or by domains such as pain, physical, or mental functioning) of OA, (4) were published between May 2006 and March 4, 2016, and (5) were in English. We excluded studies that reported costs or cost effectiveness associated with specific treatments of OA.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…We included studies if they: (1) included human patients with OA, (2) had a sample size C1000, (3) reported the cost of OA (i.e., the total cost with or without cost subcategories) and/or HRQoL (either in summary or by domains such as pain, physical, or mental functioning) of OA, (4) were published between May 2006 and March 4, 2016, and (5) were in English. We excluded studies that reported costs or cost effectiveness associated with specific treatments of OA.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The prevalence of radiographic and symptomatic knee OA was 37.4 and 12.1 %, respectively, using the Third National Health and Nutrition Examination Survey data in the USA [3]. The Framingham Osteoarthritis Study estimated that the prevalence of radiographic and symptomatic hip OA was 19.6 and 4.2 %, respectively [4]. In Canada, the prevalence of selfreported OA was 14.8 % with 10.5 % on the knee and 8.5 % on the hip [5].…”
Section: Introductionmentioning
confidence: 99%
“…These marked differences in prevalence can be attributed to differences in risk factor profiles between the populations sampled. The two largest USA-based prevalence surveys, the Johnston County Osteoarthritis Project [18] and Framingham Osteoarthritis Study [16], found prevalence rates of 10% and 4.2%, respectively. The higher prevalence in the Johnston County Project is likely due to this rural population containing a much higher proportion of farmers and African Americans, both of which are independent risk factors for hip OA [18].…”
Section: Prevalence Of Hip Oamentioning
confidence: 99%
“…Counter-intuitively, the same meta-analysis found an increased incidence of hip OA in females, although there were only two such studies used for pooling in this meta-analysis because studies looking at OA incidence are less common. The Framingham Osteoarthritis Study found a higher prevalence of radiographic hip OA in men compared to women, but no significant difference in symptomatic hip OA risk [16]. …”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…Generally, examination for OA has not been included in standard checkups, and OA has gone largely unobserved. Moreover, symptoms of OA are not correlated with radiologic findings [8,9], and severe radiological OA with pathological progression is often seen in patients who are asymptomatic or have mild symptoms.…”
Section: Introductionmentioning
confidence: 99%